Characteristics of Bronchopneumonia in Children at Dr. Abdul Rivai Regency Hospital, Berau District, East Kalimantan Province in 2022-2023 - Zalfaa Yasmine Saatirah; Arni Isnaini Arfah; Andi Husni Esa Darussalam; Muh. Alfian Jafar; Sri Wahyu (Jurnal EduHealth, 2025)
Bronchopneumonia is an inflammation that occurs in the bronchi and alveoli of the lungs and is also the most common clinical symptom of pneumonia in children. This is an infectious disease of the lower respiratory tract, often occurring in infants under 2 years of age or toddlers up to 5 years of age. The purpose of this study was to evaluate the factors that influence the incidence of bronchopneumonia in children, with a focus on risk factors, management, and the effectiveness of treatment applied in hospitals. The method used was a literature study and secondary data analysis from various journals and medical reports related to bronchopneumonia in children. The results showed that the main risk factors contributing to the incidence of bronchopneumonia in children include viral infections, incomplete immunization status, and environmental factors such as exposure to cigarette smoke. Treatment given generally includes antibiotics, fluid therapy, and supportive care, with an emphasis on early detection to prevent further complications. This study also found the importance of a holistic approach in the management of bronchopneumonia to achieve optimal outcomes in pediatric patients.